Analysis of regional growth center and hinterland in Bantul regency - Putri, Alivia Rianti; Priyadi, Unggul (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Increasing regional economic efficiency can be done through accelerated regional growth. Growth acceleration is known to produce two groups of regions, namely the growth center and Hinterland (supporting areas). This study aims to analyze the sub-districts that become growth centers and determine the value of community interaction between regions in Bantul Regency through comparative data in 2020 and 2022. In this study, secondary data is obtained through BPS Bantul Regency, which includes data, government facilities, education facilities, health facilities, worship facilities, economic facilities, communication facilities, tourism facilities, population, and distance between sub-districts. The analysis method used in this research is scalogram and gravity analysis, which was processed using Microsoft Excel. The results of the scaling analysis show that in 2020, there are five regional growth centers in Bantul Regency, which include Kasihan Subdistrict, Sewon Subdistrict, Banguntapan Subdistrict, Jetis Subdistrict, and Bambanglipuro Subdistrict. Meanwhile, in 2022, the scaling analysis shows that there are five regional growth centers in Bantul Regency, which include Banguntapan Sub-district, Sewon Sub-district, Jetis Sub-district, Kasihan Sub-district, and Kretek Sub-district. Then, the results of the gravity analysis show that there are different interaction values. The research results show that local governments need to prioritize the development of sub-districts that are still Hinterland by the RPJMD of Bantul Regency.